Penerapan Latihan Batuk Efektif untuk Mengeluarkan Sputum pada Pasien Pneumonia Lobaris Superior Dextra - Utami, Maria Putri Sari; Taukhit, Taukhit; Mustafsiroh, Nur (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the application of practical coughing exercises to expel sputum in nursing care for pneumonia patients. The research uses a case study method with evidence-based nursing, interviews, physical examination, observation, and document review. The study's results showed that after practical coughing exercises, the patient could expel retained sputum with a respiratory frequency of 20 x/minute and oxygen saturation of 100%. In conclusion, effective cough exercise therapy can positively affect pneumonia patients. Keywords: Effective cough, Pneumonia, Sputum